2021
DOI: 10.1063/5.0040914
|View full text |Cite
|
Sign up to set email alerts
|

SARS COV-2 virus-laden droplets coughed from deep lungs: Numerical quantification in a single-path whole respiratory tract geometry

Abstract: When an infected person coughs, many virus-laden droplets will be exhaled out of the mouth. Droplets from deep lungs are especially infectious because the alveoli are the major sites of coronavirus replication. However, their exhalation fraction, size distribution, and exiting speeds are unclear. This study investigated the behavior and fate of respiratory droplets (0.1–4 μ m) during coughs in a single-path respiratory tract model extending from terminal alveoli to mouth opening. An expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…Regarding the validity of simulation-generated images, previous studies have demonstrated that physiology-based simulations could sufficiently reproduce in vivo conditions [43,44]. Two numerical limitations existed in current simulations: steady flows and rigid walls, which would alter the exhaled aerosol distributions [45][46][47][48][49]. However, the differences caused by other variables could still be captured, which was the basis for classification.…”
Section: Limitationsmentioning
confidence: 99%
“…Regarding the validity of simulation-generated images, previous studies have demonstrated that physiology-based simulations could sufficiently reproduce in vivo conditions [43,44]. Two numerical limitations existed in current simulations: steady flows and rigid walls, which would alter the exhaled aerosol distributions [45][46][47][48][49]. However, the differences caused by other variables could still be captured, which was the basis for classification.…”
Section: Limitationsmentioning
confidence: 99%
“…Therefore, this modulation of the innate antiviral response induced by both host and viral factors gives a good head start to the viral replication in the URT and hyper-inflammation in the lungs, resulting in conditions that lead to COVID-19 severity. Additionally, hyper-inflammation in the respiratory bronchioles will increase the probability of airway collapse and opening, further increasing virus-laden aerosol generation [ 98 ]. As supported by recent investigation though lacking perfect experimental data, it is highly likely that the droplets and aerosols exhaled from the alveoli are more infectious than the droplets from the other airway sites and these droplets/aerosols possibly help in the airborne route of SARS-Cov-2 transmission [ 99–101 ].…”
Section: Host Virus Interaction (The Host Immune Response)mentioning
confidence: 99%
“…Respiratory disease such as coronavirus disease (COVID-19) spreads through the respiratory droplets generated by an infected subject (Modes of transmission of virus causing COVID-19 2022 ; April Si et al. 2021 ; Bhat et al. 2022 ; Yang et al.…”
Section: Introductionmentioning
confidence: 99%